Sustained hyperuricemia disrupts enterohepatic circulation through 12α-hydroxy BA and gut microbiota - Zou, Tong; Zhang, Ruixiao; Chen, Zeqing; Duan, Haiping; Wang, Zhaoguo; Gao, Ruipeng; Chen, Xin; Wang, Hongqiang; Zhao, Yue; Wang, Xiaofeng; Xing, Shichao (Frontiers in Microbiology, 2025)
Hyperuricemia (HUA) has become a worldwide health issue, drawing increasing public attention. This study aimed to elucidate the roles of bile acids (BAs) and their associations with gut microbiota in a HUA rat model. We established normal control (N) and HUA rat groups, then characterized the BA profiles in liver, serum, and ileum contents using a targeted metabolomics approach. Additionally, gut microbiota composition was analyzed through 16S rDNA gene sequencing. The results were that hyperuricemia induced elevated levels of cholic acid (CA) in liver and elevated levels of taurocholic acid (TCA), glycocholic acid (GCA), and taurodeoxycholic acid (TDCA) in the ileum content, particularly the increases in the levels of total 12α-hydroxy bile acid in the ileum content, which were consistent with the increased levels of CA in the liver. These changes are correlated to an increase in the abundance of the genera Allobaculum and Bifidobacterium. Our investigation revealed the fluxes of bile acids and their association with gut microbiota in HUA and provides new ideas for the study of metabolic diseases in hyperuricemia.